Kajian Pengaruh PH dan Berat Kertas Terhadap Sintesis dan Karakteristik Silika Fiber dari Limbah Kertas HVS dan Kardus dengan Metode Sol Gel - Ardya Pramesti Regita Cahyani; Foni Putri Sandi; Sintha Soraya Santi (Jurnal Fisika Unand, 2025)
The conversion of paper waste into silica fiber represents a strategic effort to reduce environmental pollution while adding value to HVS and cardboard waste. This study aims to examine the effect of pH and paper waste weight variations on the synthesis process and the characteristics of silica fiber produced using the sol-gel method. HVS and cardboard waste were used as cellulose sources, combined with sodium silicate and methanol. The variables tested included pH (3–7) and paper weight (8, 10, and 12 grams). Characterization involved density analysis, functional group identification using FTIR, and thermal stability assessment via TGA. The optimum condition for HVS waste was achieved at pH 5 with 8 grams, yielding a density of 1.8946 g/cm³, while for cardboard it was at pH 5 with 12 grams, yielding a density of 2.0228 g/cm³. Silanol and siloxane groups were identified in the FTIR spectra, and TGA results indicated good thermal stability at high temperatures. It can be concluded that variations in pH and paper waste weight significantly affect the formation and properties of the resulting silica fiber.